Antibodies to Borrelia burgdorferi in rodents in the eastern and southern United States. - Magnarelli, L A (1992)
Serologic studies were conducted to determine whether white-footed mice (Peromyscus leucopus) and cotton mice (Peromyscus gossypinus) contained serum antibodies to Borrelia burgdorferi, the causative agent of Lyme borreliosis. Enzyme-linked immunosorbent assays detected antibodies to this spirochete in 35.7 and 27.3% of 56 P. leucopus and 535 P. gossypinus serum samples, respectively, collected in Connecticut, North Carolina, South Carolina, Georgia, Florida, Alabama, and Mississippi. Antibody titers ranged from 1:160 to greater than or equal to 1:40,960. On the basis of adsorption tests, the antibodies detected appeared to be specific to Borrelia spirochetes. Seropositive rodents in the eastern and southern United States, areas where human cases of Lyme borreliosis have been reported, indicate a widespread geographic distribution of B. burgdorferi or a closely related spirochete.